The quality of care for adults with epilepsy: an initial glimpse using the QUIET measure - Avetisyan Ruzan; Shapiro Gabriel; Rao Jaya K; Berlowitz Dan R; Pugh Mary; Hanchate Amresh; Jarrett Kelli; Tabares Jeffrey; Kazis Lewis E (BMC, 2011)
Abstract Background We examined the quality of adult epilepsy care using the Quality Indicators in Epilepsy Treatment (QUIET) measure, and variations in quality based on the source of epilepsy care. Methods We identified 311 individuals with epilepsy diagnosis between 2004 and 2007 in a tertiary medical center in New England. We abstracted medical charts to identify the extent to which participants received quality indicator (QI) concordant care for individual QI's and the proportion of recommended care processes completed for different aspects of epilepsy care over a two year period. Finally, we compared the proportion of recommended care processes completed for those receiving care only in primary care, neurology clinics, or care shared between primary care and neurology providers. Results The mean proportion of concordant care by indicator was 55.6 (standard deviation = 31.5). Of the 1985 possible care processes, 877 (44.2%) were performed; care specific to women had the lowest concordance (37% vs. 42% [first seizure evaluation], 44% [initial epilepsy treatment], 45% [chronic care]). Individuals receiving shared care had more aspects of QI concordant care performed than did those receiving neurology care for initial treatment (53% vs. 43%; X2 = 9.0; p = 0.01) and chronic epilepsy care (55% vs. 42%; X2 = 30.2; p < 0.001). Conclusions Similar to most other chronic diseases, less than half of recommended care processes were performed. Further investigation is needed to understand whether a shared-care model enhances quality of care, and if so, how it leads to improvements in quality.